(untitled) (Annals of Medical Research, 2023)
Aim: Mild Cognitive Impairment (MCI) describes a clinical profile between healthy aging and pathological aging. Accordingly, individuals with MCI exhibit mild impairment in cognitive functions, such as memory and attention, that do not significantly affect daily life activities compared to healthy individuals of the same age. However, this condition does not meet the criteria for dementia. MCI can progress to dementia, remain stable, or return to normal cognitive status. Individuals diagnosed with MCI may develop a fear of developing dementia, leading them to search for information. YouTube is currently one of the largest and most popular databases worldwide and has become an important source of health-related information. However, the uncontrolled nature of YouTube has made its reliability controversial. Therefore, in this study, we aimed to examine YouTube videos on MCI in terms of their usefulness. Materials and Methods: The first 200 videos containing the phrase ’Mild Cognitive Impairment’ were watched by two expert neurologists. These videos were examined based on their source, content, duration, and usefulness levels. The usefulness level was determined using GQS, DISCERN, and JAMA scores. Popularity analyses were conducted using VPI. Results: Out of the 200 videos screened, 130 were included in the analysis. Of these videos, 68% were found to be very useful. The leading source of these videos was health information portals. When analyzed according to their content, videos related to the clinic of MCI were at the forefront. Conclusion: The significant number of useful videos demonstrates that the use of YouTube is an important opportunity for the dissemination of accurate and useful health information. This suggests that trust in YouTube may continue to increase.